2021
DOI: 10.1002/adtp.202100055
|View full text |Cite|
|
Sign up to set email alerts
|

Drug Repurposing for the Treatment of COVID‐19: A Knowledge Graph Approach

Abstract: Identifying effective drug treatments for COVID‐19 is essential to reduce morbidity and mortality. Although a number of existing drugs have been proposed as potential COVID‐19 treatments, effective data platforms and algorithms to prioritize drug candidates for evaluation and application of knowledge graph for drug repurposing have not been adequately explored. A COVID‐19 knowledge graph by integrating 14 public bioinformatic databases containing information on drugs, genes, proteins, viruses, diseases, sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Fang et al [71] suggested a head-and-tail entity fusion model, which obtained 97% accuracy while fusing data from diverse sources. Yan et al [104] created a COVID-19 KG by integrating 14 publicly available bioinformatic databases comprising information on medications, genes, proteins, viruses, illnesses, and symptoms and their associations. They utilized the DrugBank ID for each drug, the National Center for Biotechnology Information gene ID for each gene, and the MeSH ID for each disease because they are all standardized.…”
Section: Knowledge Fusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fang et al [71] suggested a head-and-tail entity fusion model, which obtained 97% accuracy while fusing data from diverse sources. Yan et al [104] created a COVID-19 KG by integrating 14 publicly available bioinformatic databases comprising information on medications, genes, proteins, viruses, illnesses, and symptoms and their associations. They utilized the DrugBank ID for each drug, the National Center for Biotechnology Information gene ID for each gene, and the MeSH ID for each disease because they are all standardized.…”
Section: Knowledge Fusionmentioning
confidence: 99%
“…However, combining various reasoning models is also a successful strategy; Yan et al [104] employed motifbased graph analysis (GM-based) and KG embedding (KRL-based) to compute the scores for candidate drugs independently and then combine them using a linear function.…”
Section: Reasoning Based On Krlmentioning
confidence: 99%
“…In their conclusion, they recommended using a classifier developed on PubMed-BERT (a variant of BERT which is a transformer-based machine learning technique) to construct a COVID-19 knowledge graph and then applying TransE (a neural knowledge graph completion algorithm) to predict drug repurposing candidates. Yan et al [13] constructed a knowledge graph by integrating 14 public bioinformatic databases containing information on drugs, genes, proteins, viruses, diseases, and symptoms and developing their linkages; and then generated and ranked drug candidates for repurposing as treatments for COVID-19 by integrating motif scores, PageRank scores, and embedding scores for each drug. Al-Saleem et al [14] constructed the "CAS Biomedical Knowledge Graph" using data from the "CAS Content Collection" and other public repositories; and then used their own result ranking method to predict potential drug repurposing candidates for COVID-19.…”
Section: Related Workmentioning
confidence: 99%
“…A similar study was carried out by Zhou et al [ 61 ], where high-value proteins and drug combinations were derived by a network-based algorithm. Yan et al proposed a knowledge graph approach to prioritise drug candidates against SARS-Cov-2 [ 62 ]. This study integrated 14 biological databases of drugs, genes, proteins, viruses, diseases, symptoms and their linkages, and developed a network-based algorithm to extract hidden linkages connecting drugs and COVID-19 from the constructed knowledge graph.…”
Section: Mining Patient Data and Drug Repurposingmentioning
confidence: 99%
“…Motif-clique discovery algorithms are used to extract these defined motifs-of-interest. Credit: Yan et al /Wiley [ 62 ]. (Online version in colour.)…”
Section: Mining Patient Data and Drug Repurposingmentioning
confidence: 99%